Autophagy as a dual-faced host response to viral infections - Zhai, Huanjie; Wang, Tao; Liu, Di; Pan, Li; Sun, Yuan; Qiu, Hua-Ji (Frontiers in Cellular and Infection Microbiology, 2023)
Autophagy selectively degrades viral particles or cellular components, either facilitating or inhibiting viral replication. Conversely, most viruses have evolved strategies to escape or exploit autophagy. Moreover, autophagy collaborates with the pattern recognition receptor signaling, influencing the expression of adaptor molecules involved in the innate immune response and regulating the expression of interferons (IFNs). The intricate relationship between autophagy and IFNs plays a critical role in the host cell defense against microbial invasion. Therefore, it is important to summarize the interactions between viral infections, autophagy, and the host defense mechanisms against viruses. This review specifically focuses on the interactions between autophagy and IFN pathways during viral infections, providing a comprehensive summary of the molecular mechanisms utilized or evaded by different viruses.